ANALISIS YURIDIS TENTANG TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI INTERNET DIKAITKAN DENGAN KEBEBASAN PERS - Rudolf Silaban; Jaminuddin Marbun (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2020)
This study ims at finding out and understanding the provisions in the provisions of Indonesian law regarding the relation to defamation through the internet associated with press freedom, forms and criteria for criminal acts of defamation carried out in the internet media, forms of accountability for perpetrators of criminal defamation of names both through the internet in the applicable legal provisions in Indonesia. This research is a normative juridical research that is descriptive analytical and data analysis is carried out qualitatively descriptive, normative, logical, systematic, using deductive and inductive methods. The results of the study show that the regulation in the provisions of Indonesian law regarding the relation to defamation through the internet is related to freedom of the press. In a criminal case involving the press, of course, it cannot necessarily use the law against the law contained in the Criminal Code because a journalist's work is protected by Law No. 40 of 1999 concerning the Press. If there is a use of criminal legal instruments, then the element of unlawfulness contained in the Criminal Code must be linked to the Press Law. The forms and criteria for criminal defamation with complaints, insults to official bodies, insults to the dead. The forms of liability of perpetrators of criminal defamation through the internet in the provisions of applicable law in Indonesia, namely liability for criminal defamation through the internet media can be applied along with imprisonment sanctions or in the form of fines in accordance with applicable laws. This liability is charged in accordance with the criminal element which has been reviewed in terms of terms of criminal liability.